The Education Crisis in Conflict Zones: A Case Study on the Impact of Political Instability on the Sustainability of School - Olaniyi Jibril, Ayuba (Universitas Nurul Jadid, 2024)
This study focuses on the educational challenges faced by schools serving internally displaced children in Northeast Nigeria, particularly related to the shortage of qualified teachers, infrastructure crises, and reliance on external aid. The primary objective of this research is to explore and analyze the impact of these factors on the quality of education provided in these schools, as well as to identify opportunities for improvement. The research methodology employed is qualitative, utilizing a case study approach that involves in-depth interviews, participatory observations, and document analysis across three different schools in the Borno region. The findings reveal that the lack of formally trained teachers significantly affects the quality of instruction, which is further exacerbated by inadequate infrastructure and a high dependency on external aid for educational materials. The implications of this study highlight the need for more coordinated and sustainable interventions, which not only rely on external support but also focus on strengthening the internal capacities of schools, including teacher training and infrastructure improvement. This research is expected to make a meaningful contribution to efforts aimed at strengthening the educational system in crisis areas and ensuring that the right of children to receive quality education is upheld.